Proteomic Analysis of Caspofungin-Induced Responses in Planktonic Cells and Biofilms of Candida albicans - Li, Peng; Seneviratne, Chaminda J.; Luan, Qingxian; Jin, Lijian (Frontiers in Microbiology, 2021)
Candida albicans biofilms display markedly increased antifungal resistance, and the underlying mechanisms remain unclear. This study investigated the signature profiles of C. albicans planktonic cells and biofilms in response to caspofungin (CAS) by mass spectrometry-based shotgun proteomics. We found that C. albicans biofilms were two-fold more resistant to CAS with reference to planktonic cells. Notably, 9.6% of C. albicans biofilm cells survived the lethal treatment of CAS (128 µg/ml), confirmed by LIVE/DEAD staining, confocal laser scanning microscopy and scanning electron microscopy analyses. The responses of C. albicans planktonic cells and biofilms to CAS treatment at respective minimum inhibitory concentrations were assessed by high-throughput proteomics and bioinformatics approaches. There were 148 and 224 proteins with >2-fold difference identified from the planktonic cells and biofilms, respectively. CAS treatment downregulated several cell wall- and oxidative stress- related proteins. Whereas, CAS-induced action was compensated by markedly increased expression of many other proteins involved in cell wall integrity and stress response (e.g., heat shock proteins). Moreover, considerable expression changes were identified in metabolism-associated proteins like glycolysis, tricarboxylic acid cycle and ATP biosynthesis. Importantly, various key proteins for cell wall integrity, stress response and metabolic regulation (e.g., PIL1, LSP1, HSP90, ICL1 and MLS1) were exclusively enriched and implicated in C. albicans biofilms. This study demonstrates that C. albicans biofilms undergo highly complicated yet complex regulation of multiple cellular pathways in response to CAS. Signature proteins essential for modulating cell wall integrity, stress response and metabolic activities may account for the antifungal resistance of C. albicans biofilms.